2017
DOI: 10.1111/jcpe.12724
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes mellitus/hyperglycaemia and peri‐implant diseases: Systematic review and meta‐analysis

Abstract: Within its limits that demand great caution when interpreting its findings, this systematic review suggests that diabetes mellitus/hyperglycaemia is associated with greater risk of peri-implantitis, independently of smoking, but not with peri-implant mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
183
1
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(201 citation statements)
references
References 80 publications
1
183
1
16
Order By: Relevance
“…9,10,12,25 In the following step (Model 3), the relevant variables of osteoporosis, Eichner index, bruxism, jaw position, surgical procedure, GBR, fixation method, connection type, KMW, and superstructure design were added. The explanatory variables were input to each model according to the following steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,12,25 In the following step (Model 3), the relevant variables of osteoporosis, Eichner index, bruxism, jaw position, surgical procedure, GBR, fixation method, connection type, KMW, and superstructure design were added. The explanatory variables were input to each model according to the following steps.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,12,25 It has been reported that implant treatment for patients with well-controlled diabetes can be acceptable. 9,10,12,25 It has been reported that implant treatment for patients with well-controlled diabetes can be acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the patient is well‐controlled, implant survival is comparable to that of healthy subjects; peri‐implant health is good and peri‐implant bone loss is comparable to controls (Abduljabbar, Javed, Malignaggi, Vohra, & Kellesarian, ; Al Amri et al., , ; de Araújo Nobre, Maló, Gonçalves, Sabas, & Salvado, ; Kotsakis et al., ; Monje, Catena, & Borgnakke, ; Shi, Xu, Huo, Cai, & Liu, ). In subjects with hyperglycemia, that is, less well‐controlled diabetics, the risk of developing peri‐implantitis has been shown to be increased (Monje et al., ; Turri et al., ), although other studies did not observe such an effect (Eskow & Oates, ). Antibiotic prophylaxis is recommended in diabetic patients, in particular for patients with higher glycemic levels.…”
Section: Diabetes Mellitusmentioning
confidence: 97%
“…Their findings have led to a more rigorous and open scientific investigation of the impact systemic factors have on implant therapy success. It is a positive sign that several recent investigations have begun to focus not only on implant survival, but also on implant‐related biologic complications, including long‐term implant maintenance and the potential consequences of implant therapy under function within the oral environment (Table ) . Recent systematic reviews have begun to address the potential for long‐term implant sequelae associated with diabetes (Table ) .…”
Section: The Impact Of Glycemic Control On Successful Implant Treatmentmentioning
confidence: 99%